Responsabilidad social: un acercamiento a la perspectiva de los ejecutivos peruanos - Jáuregui Machuca, Kety (2012)
In recent years the issue of social responsibility is becoming more important, which is reflected in the companies have incorporated it into their agenda of interests. In this sense, the article is intended to make a first approach to the level of implementation efforts, as well as their prospects for the future. We interviewed a total of 144 people representing different economic sectors. We conclude that the majority of executives do not have a clear understanding of the modern concept of RS nor of its benefits, it limits the concept to philanthropy and actions are oriented to the community and environment.